MEDIA RELATIONS STRATEGY of HOTEL NEO + AWANA YOGYAKARTA IN BUILDING BRAND IMAGE - Saputri, Chusnina Dwi (The Indonesian Journal of Communication Studies, 2018)
The high growth of hotels in Yogyakarta caused a fierce competition with each other, thus demanding a strategy to survive in the midst of intense competition. One of the strategies that used by the hotel is media relations strategy. This study discus about media relations strategy of Hotel Neo+ Yogyakarta in building its brand image. The goal is to find out how media relations strategy that built by Neo+ Awana Hotel Yogyakarta’s public relations in building its brand image. In this study, the author found that public relations at Neo+ Awana Hotel Yogyakarta not specifically put in a division, but the field of sales & marketing division operate the media relations activities. Media relations strategy run by Hotel Neo + Awana manifested in from creating actual event, introduction with press conference, public relations intimacy with media and facilitating media. The media relations strategy had done with the aim to get a positive image of the company in the eyes of the public.